2016
DOI: 10.1037/xap0000069
|View full text |Cite
|
Sign up to set email alerts
|

With practice, keyboard shortcuts become faster than menu selection: A crossover interaction.

Abstract: It is widely believed that a graphical user interface (GUI) is superior to a command line interface (CLI) for novice users, but less efficient than the CLI after practice. However, there appears to be no detailed study of the crossover interaction that this implies. The rate of learning may shed light on the reluctance of experienced users to adopt keyboard shortcuts, even though, when mastered, shortcut use would reduce task completion times. We report 2 experiments examining changes in the efficiency of and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Consistent with previous studies, this study confirmed that older adults have a major problem with using semantically distant or complex icons due to difficulties in building and applying accurate mental models between the graphical item and its operational meaning (Action 8,(19)(20)(21)(22)(23) (Leung, McGrenere, and Graf 2011;Remington, Yuen, and Pashler 2016). Specifically, most of the difficulties occurred when participants did not understand the graphical meaning of icons.…”
Section: Assisted Navigation Buttonssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, this study confirmed that older adults have a major problem with using semantically distant or complex icons due to difficulties in building and applying accurate mental models between the graphical item and its operational meaning (Action 8,(19)(20)(21)(22)(23) (Leung, McGrenere, and Graf 2011;Remington, Yuen, and Pashler 2016). Specifically, most of the difficulties occurred when participants did not understand the graphical meaning of icons.…”
Section: Assisted Navigation Buttonssupporting
confidence: 89%
“…It greatly reduces cognitive load for senior users. In this way, we believe that with practice, icons and buttons could become an easier and faster way of using the shortcut for older adults, which has also been reported in computer use (Remington, Yuen, and Pashler 2016). Therefore, we recommend that:…”
Section: Enhance the Visual Differences Between Touchable And Non-tou...mentioning
confidence: 84%
“…The simplest way to interact with radiology workstation software is to use graphical user interface (GUI) elements such as buttons and drop-down menus, which require a mouse to be used as an input device. This mode of interaction with software is considered inefficient and is best suited for inexperienced users (22)(23)(24)(25).…”
Section: Conventional Setupmentioning
confidence: 99%
“…Luo et al developed Automated Machine-Learning (Auto-ML) to automate the whole machine learning process and support patients’ outcome predictions [ 96 ]. In this context, graphical user interfaces (GUI) may support inexperienced users in respect to a command line interface (CLI) [ 97 ].…”
Section: Big Data Production Big Data Analysis and Data Integratimentioning
confidence: 99%